Serum erythropoietin levels in patients with central serous chorioretinopathy - Turgut, Burak; Ilhan, Nevin; Uyar, Fatma Yayla; Celiker, Ulku; Demir, Tamer; Koca, Suleyman Serdar (Dove Medical Press Ltd, 2010)
Objective: To evaluate the levels of erythropoietin (EPO) in the serum in patients with central serous chorioretinopathy (CSC). Methods: An institutional comperative clinical study. The serum EPO levels were measured with the enzyme- linked immunosorbent assay (ELISA) method, of 15 patients with active CSC (Group 1), 15 patients with inactive CSC (Group 2) and 15 healthy volunteers (Group 3). Kruskal- Wallis variance analysis and Mann-Whitney U test were used for statistical analysis. Results: The patient and control groups were matched for age and sex. There was no statistically significant variation with regard to age and gender among the groups (P > 0.05). The mean serum EPO concentrations in patients with active CSC (Group 1), inactive CSC (Group 2) and in healthy controls (Group 3) were 11.39 +/- 3.01 mlU/mL, 11.79 +/- 3.78 mlU/mL and 11.95 +/- 3.27 mlU/mL, respectively. There was no significant variation among the serum EPO concentrations of the study groups (P > 0.05). Conclusion: These findings suggest no role of serum EPO in pathogenesis of CSC.
Keywords: Central serous chorioretinopathy; erythropoietin; serum